The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1051/0004-6361:20066984
|View full text |Cite
|
Sign up to set email alerts
|

AreSwiftgamma-ray bursts consistent with the Ghirlanda relation?

Abstract: A few tight correlations linking several properties of gamma-ray bursts (GRBs), namely the spectral peak energy, the total radiated energy, and the afterglow break time, have been discovered with pre-Swift GRBs. They were used to constrain the cosmological parameters, together with type-Ia supernovae. However, the tightness of these correlations is a challenge to GRB models. We explore the effect of adding Swift bursts to the Ghirlanda and Liang-Zhang relations. Although they are both still valid, they become … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…Furthermore these very luminous GRBs with high values of the redshift corrected E peak are not compatible with the E peak,i − E γ relationship as shown in Fig. 13 which was obtained for GRBs with in general lower values of the peak energy (Ghirlanda et al 2004;Campana et al 2007). While being consistent with the Amati (E peak,i − E iso ) relation at the 2σ level (see also Amati et al 2009), albeit with a large scatter (see also e.g.…”
Section: Afterglow Properties and Energeticsmentioning
confidence: 73%
“…Furthermore these very luminous GRBs with high values of the redshift corrected E peak are not compatible with the E peak,i − E γ relationship as shown in Fig. 13 which was obtained for GRBs with in general lower values of the peak energy (Ghirlanda et al 2004;Campana et al 2007). While being consistent with the Amati (E peak,i − E iso ) relation at the 2σ level (see also Amati et al 2009), albeit with a large scatter (see also e.g.…”
Section: Afterglow Properties and Energeticsmentioning
confidence: 73%
“…Thus, particular care and sophisticated statistical methodologies have to be adopted in order to avoid circularity problems when constructing a GRB Hubble diagram. In addition, recent analyses based on updated samples of GRBs showed that the dispersion of three‐parameter correlations could be significantly larger than thought before (Campana et al 2007; Ghirlanda et al 2007; Rossi et al 2008).…”
Section: Introductionmentioning
confidence: 90%
“…curves, the measurement of t b and its use to derive the jet opening angle are questionable (Campana et al 2007;Ghirlanda et al 2007). It was also proposed that the inclusion of the "high signal timescale", T 0.45 , introduced and used for variability studies, reduces the dispersion in the E p,i -E iso correlation , but this property was not confirmed by later studies (Rossi et al 2008;Collazzi & Schaefer 2008).…”
Section: Grb 080916c and Other Spectral Energy Correlationsmentioning
confidence: 99%